Evaluation of Ergonomic Conditions with Notch Sensor Used in the Electronics Industry of Mexicali, Mexico - González, Carlos Raúl Navarro; Sánchez, Juan Carlos Quiroz; Ortiz, Alicia López; González, Yanet Villarreal; Zepeda, Pedro Alberto Escárcega; Alarcón, Rigoberto Zamora; Corona, Ana Laura Sánchez (Advanced Aspects of Engineering Research Vol. 1, 2021)
An analysis of mathematical and biomechanical simulation of a system that represents movements of the human body at the time of developing activities of various operations was made. The most important part of the study, contemplated the use of Notch sensors placed in various parts of the human body to measure different positions of positions in various functions. The investigation consisted of three stages, the first being an analysis of movements of people in an industrial process of welding operation in small electronic circuit systems used in cellular telephony of a company located in the city of Mexicali. The second was a biomechanical simulation of a wooden structure with movable parts in the sagittal plane of the biomechanical analysis and the third a statistical analysis with the regression and correlation process to obtain a mathematical model that represented, various positions of the activities of the first step, and an effect of discomfort or serious health symptoms. With the results obtained, was made an evaluation to reduce labor accidents due to fatigue by at least 50%, being that Notch sensors, whose movement signals can be presented on a cell phone, having better effectiveness. The investigation was carried out from January 2018, until June 2019.